Brincar, atividade humana e ferramenta pedagógica no contexto escolar da região metropolitana de natal - Estácio, Mércia Maria de Santi (2014)
This thesis talks about the use of guided educational tools in play and playful in public schools in the Metropolitan Region of Natal (MRN), contributing to the teaching and students learning of basic education in the contents of portuguese and mathematics. We assume that the play is an activity / human need and therefore implies the proper development of children in physical, psychological, biological, cultural, social and historical aspects. We consider the mediation exercised by the teacher in the classroom, and the affection existing between teacher and student, sine qua non terms, so that the truth and fact of the process of teaching and learning occur. Thus, theoretically collaborated Paulo Freire, with his dialogical vision; Lev S. Vygotsky says that we learn and why we develop; Lev S. Vygotsky that states that we learn and for that we develop ourselves; Pierre Bourdieu and the concept of habitus, as something embedded and therefore procedural, and the cultural capital that needs to be fed and (re)meaning at school; Luiz Pereira, Bernard Lahire, Gilles Brougère and others brought their theoretical contributions. The empirical field of research was composed by the Municipal School Professor Ulysses de Góis, located in the neighborhood of Nova Descoberta in Natal, and the Municipal School José Horacio de Góis, located in the community of Guanduba, in São Gonçalo do Amarante, municipalities of the Metropolitan Region of Natal (MRN). We used as methodology the collaborative-action-research as a possible of effective participation of the research subjects, imputing them a voice and performance in the process, and not considering them just observers. The results indicate the effectiveness of the pedagogical tools in play and playful to the learning of students, but that alone is not able to solve all the problems of the school, other referrals need to be secured, as the planning of the actions to be developed in the school and in the classroom, systematized pedagogical orienttion for faculty, family participation/involvement in the school life of students, among other actions that need to be weighted so that education fulfills its role and promote the emancipation of the subject, because in the freireana liberating perspective, "the reading of the world preced the lecture of the word"